Essentials of strategic management - Pitt Martyn; Koufopoulos, Dimitrios (New Delhi Sage Publications, 2023)
About the Book: Essentials of Strategic Management This exciting new textbook is built on the belief that strategic management principles are more straightforward than they seem. Unlike other textbooks, it does not overcomplicate the discussion with enigmatic layers of theory or irrelevant perspectives from other disciplines. Instead, you will find focused, clearly articulated coverage of the key topics of strategic management, encouraging critical reflection and deeper exploration on your own terms. Fully developed to cover the essentials of any strategic management course, this textbook not only creates understanding of the principles of strategy but shows you how to apply them constructively in the face of real-world practicalities. Throughout the text, these principles are put into context with illustrations and examples drawn from all over the world and from all kinds of organization - from Shell, Airbus and Tesco to small and non-profit enterprises. With an emphasis on topical, distinctive and engaging features, this text offers: Over 120 short, topical case studies drawn from every type of organization across more than 20 countries, written especially for this book and supplemented with questions and tasks. Worksheets for strategy analysis that can be used to tackle real-world situations Learning outcomes, key points and summaries to focus your reading on what matters Chapter-by-chapter exercises for further study and discussion Suggestions for further reading to deepen your understanding of the theories underpinning the chapters In addition, tutors will benefit from a fully developed companion website offering lecture slides, teaching notes for case studies and assignments, module plans and links to further reading.www.sagepub.co.uk/pit Contents Preface The Essence of Strategy and Strategic Management Understanding the External Environment Industry Sector Environments Enterprise Stakeholders, Identity and Purpose Enterprise Resources Distinctive Capabilities Strategic Decision-M
Keywords: Strategic Management